ANALISIS KUALITAS BUTIR SOAL TES BUATAN GURU MATA PELAJARAN MATEMATIKA JURUSAN AKUNTANSI KELAS X SMK NEGERI 1 MANGANITU SELATAN - Tilaar, Anetha Lyta Flora; Sulangi, Victor; Madalise, Adrianus (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. This research aims to analyze the quality of test items made by mathematics teachers majoring in accounting in class X SMK Negeri 1 Manganitu Selatan in terms of validity, reliability, discrimination power, level of difficulty, and the  effectiveness of distractors. This type of research is a descriptive study. The subjects in this study were all students of 10th gradersof Accounting calss of SMK Negeri 1 Manganitu Selatan. Technique of data collection is done by documentation. The data obtained is processed manually using the Microsoft Excel 2013 program.  Results,  concluded that the quality of the items made by the teacher of mathematics majoring in accounting in class X SMK Negeri 1 Manganitu Selatan were: there are 10 or 40% of good quality questions, 7 or 28% of poor quality questions, and 8 or 32% of questions, not good quality. Questions that have good quality can be stored in the question bank to be used again, questions that have poor quality need to be revised and for questions that have poor quality, it should be discarded. Keywords: Item analysis, dicrimiation power, the effectiveness of distractors, reliability, level of difficulty, validity.